Secular variations in seawater chemistry controlling dolomitization in shallow reflux systems: insights from reactive transport modelling. Issue 5 (1st April 2016) - Gabellone, Tatyana; Whitaker, Fiona
Abstract: Dolomitization often plays a critical role in the pore network development of platform carbonates, with implications for reservoir quality distribution. Understanding both the hydrological system driving dolomitization and the chemistry of the fluids involved is fundamental to constrain predictions of the geometry and the petrophysical properties of dolomite bodies. Here, the role of secular variations in seawater Mg/Ca as a control on dolomitization and early porosity modification was evaluated using one‐dimensional reactive transport models and fluids based on modern (aragonite sea), Mississippian and Aptian (calcite sea) seawaters. The sensitivity of dolomitization to a range of extrinsic controls (brine salinity, temperature, fluid flow rate and pCO2 ) and to intrinsic reactivity of the sediments (effective reactive surface area) was also explored. Simulations suggest faster calcite replacement by dolomite for seawaters with higher Mg/Ca, indicating that dolomitization potential is determined more by Mg/Ca rather than saturation index. Increasing evaporative concentration enhances reaction rate independent of the effect of enhanced density‐driven fluid flux. In addition to brine composition, effective surface area of precursor sediments and temperature exert a critical control on replacement rate, while secular variations of pH and carbonate alkalinity associated with changes in pCO2 are only secondary controls. Above flow rates of 0·01 m yr −1 replacive dolomitization is reaction‐limited rather than flux limited, favouring alteration of fine‐grained carbonates and suggesting that preferential alteration of grainstone units is rare unless head gradients are low. Post‐replacement dolomite cementation is flux dependent, and thus favoured in areas of high head gradient and high permeability sediments and, contrary to replacement, supersaturation is a more important driver than Mg/Ca. While uncertainties remain regarding low‐temperature dolomitization kinetics, the capability of numerical simulations to decouple individual controls provides new insights which can be used, in conjunction with traditional comparative sedimentology, to generate more rigorous conceptual models for individual reservoir settings.